Identification of murine phosphodiesterase 5A isoforms and their functional characterization in HL‐1 cardiac cell line. Issue 1 (18th May 2017) - Campolo, Federica; Zevini, Alessandra; Cardarelli, Silvia; Monaco, Lucia; Barbagallo, Federica; Pellegrini, Manuela; Cornacchione, Marisa; Di Grazia, Antonio; De Arcangelis, Valeria; Gianfrilli, Daniele; Giorgi, Mauro; Lenzi, Andrea; et al.
Abstract : Phosphodiesterase 5A (PDE5A) specifically degrades the ubiquitous second messenger cGMP and experimental and clinical data highlight its important role in cardiac diseases. To address PDE5A role in cardiac physiology, three splice variants of the PDE5A were cloned for the first time from mouse cDNA library (mPde5a1, mPde5a2, and mPde5a3). The predicted amino acidic sequences of the three murine isoforms are different in the N‐terminal regulatory domain. mPDE5A isoforms were transfected in HEK293T cells and they showed high affinity for cGMP and similar sensitivity to sildenafil inhibition. RT‐PCR analysis showed that mPde5a1, mPde5a2, and m Pde5a3 had differential tissue distribution. In the adult heart, m Pde5a1 and m Pde5a2 were expressed at different levels whereas m Pde5a3 was undetectable. Overexpression of mPDE5As induced an increase of HL‐1 number cells which progress into cell cycle. mPDE5A1 and mPDE5A3 overexpression increased the number of polyploid and binucleated cells, mPDE5A3 widened HL‐1 areas, and modulated hypertrophic markers more efficiently respect to the other mPDE5A isoforms. Moreover, mPDE5A isoforms had differential subcellular localization: mPDE5A1 was mainly localized in the cytoplasm, mPDE5A2 and mPDE5A3 were also nuclear localized. These results demonstrate for the first time the existence of three PDE5A isoforms in mouse and highlight their potential role in the induction of hypertrophy. Abstract : To address PDE5A role in cardiac physiology, three splice variants of the PDE5A were cloned for the first time from mouse cDNA library (mPde5a1, mPde5a2, and mPde5a3). Overexpression of mPDE5As induced cell cycle progression of HL‐1 cells. mPDE5A1 and mPDE5A3 overexpression increased the number of polyploid and binucleated cells, mPDE5A3 widened HL‐1 areas, and modulated hypertrophic markers more efficiently respect to the other mPDE5A isoforms.